DAMPAK RELOKASI PEDAGANG KAKI LIMA ( PKL ) PASAR JONGKOK KE MTC GIANT PANAM TERHADAP KEHIDUPAN SOSIAL EKONOMI PEDAGANG - Abdul Rahman; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was carried out on the public street vendors (PKL) who relocated to the area MTC Giant Panam. Problems studied in this research is how the impact of the relocation of street vendors to MTC Giant Markets Squatting on the socio-economic life of the merchant.The purpose of this study is to find out who the vendors who sell at area Giant Panam MTC, to determine the response to the relocation of street vendors to market MTC Giant Panam area, and to determine the impact of the relocation of street vendors (PKL) Squatting Market area to MTC Giant Panam towards the socio-economic life of the merchant. The population in this study are street vendors who relocated to the area MTC Giant Panam 250 people, 25 people were taken as samples by using random sampling techniques.In the authors use data collection methods of interviews and observations, and analyzed using quantitative descriptive method, that is by depicting or describing phenomena problems studied in the form of numbers, then processed using the percentage tables, so it can be clearly understood conclusion.Based on the results of the study authors note that the street vendors who sell at area Giant Panam MTC is a street vendor who initially conduct trading activities along Jl. HR. Soebrantas Panam, relocation of the market to get a good response from vendors who sell in the area MTC Giant Panam, and relolasi market impact or influence both the social and economic life of street vendors, among which a good trade competition among fellow traders in develop business for goods and services traded, social interactions are good, and the high level of earned income traders in buying and selling activities.Keywords: street vendors, social, and economic life of a trader